Increasing the Attractiveness of Engineering Education in the Area of Electronic Communications - Hrad, J.; Zeman, T. (Elektronika ir Elektrotechnika, 2010)
Engineering education is not an isolated “ivory tower” that could remain unchanged for years – it has to reflect changes in society and technology, to which it is linked tightly. The question is what innovative topics should be introduced to students and how the education process should be made more attractive. This is even more important in a situation when we can observe decreasing interest in technical sciences and inclination towards humanities. The purpose of this paper is to analyze the current situation in the specific conditions of European technical universities, particularly in the area of electronic communications, to predict the development in several coming years, and to propose suitable approaches in terms of specific topics and methods.